THE CONSUMPTION OF MINERAL FERTILIZERS AND WATER RESOURCES QUALITY IN THE EUROPEAN UNION AND THE REPUBLIC OF SERBIA - Roljević, Svetlana; Nikolić, Aleksandra; Tepavac, Rajko (Economics of Agriculture, 2012)
Its goal is to point out to a significance of tracking the nitrate emission in agricultural production, by which makes bases for undertaking adequate measures of water protection and other natural resources from agriculture effect. This paper is focused on analysis of mineral, i.e. nitrogen fertilizers consumption, and their effect on the environment, i.e. surface waters. Data from the relevant institutions in the EU on consumption of mineral fertilizers and loading of waters by nitrates, which origin from agricultural production, were collected by desk research method. Data on consumption of mineral fertilizers in the Republic of Serbia for the period 1985-2001. year are taken from official statistics for selected years, while the display of water quality data is given for research by local authors. As a general conclusion imposes a fact that in our country have been spent significantly less amounts of mineral fertilizers in relation to the community of 27 countries, but there is still a profound adverse impact on the environment owing to inadequate laws implementation and lack of infrastructure in the field of ecology.